Volume 2: Combustion, Fuels and Emissions, Parts a and B 2010
DOI: 10.1115/gt2010-23059
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Non-Premixed Bluff Body-Stabilized Flames in Heated Air Flow

Abstract: This paper describes a study of the fundamental flame dynamic processes that control bluff body-stabilized combustion of liquid fuel with low dilatation. Specifically, flame oscillations due to asymmetric vortex shedding downstream of a bluff body (i.e., the Be´nard/von-Ka´rma´n vortex street) were characterized in an effort to identify the fundamental processes that most affect the intensity of these oscillations. For this purpose, the spatial and temporal distributions of the combustion process heat release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Concurrent fuel injection from the cylinder trailing face into the primary vortex, resulting in a non-premixed configuration, is also documented under the same conditions, and the respective performances are compared. The above configuration lends itself to the examination of various forms of fuel injection and flame development under the action of a dynamically evolving mixing field (Bakrozis et al, 1999;Kim et al, 2010;Cross et al, 2010;Ohiwa et al, 1994;Shanbhouge et al, 2009), while it is also appropriate for model development and validation (Baudoin et al, 2009;Giacomazzi et al, 2004;Papailiou et al, 2000). Partial fuel premixing and stratification are currently being investigated as a core strategy for meeting the combined constraints of anticipated fuels, pollutant emissions, fuel consumption, and stability through optimum control of mixture placement (Tuttle et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Concurrent fuel injection from the cylinder trailing face into the primary vortex, resulting in a non-premixed configuration, is also documented under the same conditions, and the respective performances are compared. The above configuration lends itself to the examination of various forms of fuel injection and flame development under the action of a dynamically evolving mixing field (Bakrozis et al, 1999;Kim et al, 2010;Cross et al, 2010;Ohiwa et al, 1994;Shanbhouge et al, 2009), while it is also appropriate for model development and validation (Baudoin et al, 2009;Giacomazzi et al, 2004;Papailiou et al, 2000). Partial fuel premixing and stratification are currently being investigated as a core strategy for meeting the combined constraints of anticipated fuels, pollutant emissions, fuel consumption, and stability through optimum control of mixture placement (Tuttle et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…However, studies of direct (Bakrozis et al, 1999;Kim et al, 2010;Ohiwa et al, 1994) or indirect (Cross et al, 2010) fuel injection into the wake of planar center-bodies have emphasized the suitability of the planar fuel-injected arrangement for highlighting the interactions between the large-scale vortex development, the fuel injection process, the spatial mixture variation, and their effects on stability, heat release, and emissions. This is also an important configuration for evaluating models and developing practical injectors from struts, such as in some stationary gas turbines, afterburners, furnaces, and utility or household burners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed experimental setup uses a number of circular fuel injection orifices located just upstream of the flameholder's trailing edge that injected liquid fuel into the crossflow. Earlier studies [4,5] showed that the flame structure generated in this problem dramatically differed from that attained in the premixed case that used the same bluff-body to stabilize a combustible mixture. Eor the case of closely coupled fuel injection, high-speed imaging suggested that the reaction takes place in stable, stoichiometric flamelets, distributed over a relatively large reaction zone existing throughout the wake flow behind the bluff-body.…”
Section: Introductionmentioning
confidence: 89%
“…Figure 4 (taken from Ref. [4]) shows the flame images extracted from high-speed movies of premixed and nonpremixed bluff-body stabilized combustion processes. These images show the fundamental difference in flame structure between these flames.…”
Section: Description Of Bluff-body Flow and Combustion Processesmentioning
confidence: 99%